DOI: 10.11606/t.76.2017.tde-06012017-093322
|View full text |Cite
|
Sign up to set email alerts
|

Estudos de primeiros princípios da adsorção de água e de etanol sobre ligas de superfície de metais de transição sob efeitos de deformação expansiva e compressiva

Abstract: AgradecimentosPrimeiramente, agradeço à todos aqueles que de alguma forma contribuíram para a finalização de mais esse projeto em meu caminho: Minha família no todo, aos amigos de perto, de longe, de bem longe e aos meus professores. Agradeço sem citar nomes, mas saibam que foram essenciais em muitos momentos dessa etapa.Agradeço ao meu orientador Prof. Dr. Juarez L. F. Da Silva, que desde o ínicio se mostrou preocupado com minha formação e o prosseguimento de minha carreira. Foi quem possibilitou novas oportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…This value is 12.5 % higher than the default recommended value for the O atom, the most demanding in terms of number of plane waves, which is related to its s and p states. The cutoff energies were different than 489 eV in the following exceptions: (i) to optimize crystal lattice parameters, through calculation of the stress tensors and minimization of the forces on each atom changing the volume of the unit cell, a higher multiplier was applied for the recommended cutoff (2 times the default value, instead of 1.125 times, for each metal), due to the slower convergence of the stress tensor with respect to the basis set, which was tested in a previous study done by other authors; 133 (ii) to calculate the clean surface properties discussed in Chapter 6 the cutoff was adjusted to be 12.5 % higher than the required cutoff for each metal (for example, 402, 282 and 280 eV were employed, respectively, to calculate the clean Ni(111), Pd(111) and Pt(111) surface properties), since there is no need to comply with a higher cutoff in a self-contained investigation of the clean surface properties; (iii) the results shown in Chapter 3 employed a cutoff energy 12.5 % higher than the recommended cutoff, ENMAX, for each metal, since the O atom was not studied in the referred chapter.…”
Section: Adjusting the Cutoff Energy For The Basis Set And Sampling The Brillouin Zonementioning
confidence: 99%
See 3 more Smart Citations
“…This value is 12.5 % higher than the default recommended value for the O atom, the most demanding in terms of number of plane waves, which is related to its s and p states. The cutoff energies were different than 489 eV in the following exceptions: (i) to optimize crystal lattice parameters, through calculation of the stress tensors and minimization of the forces on each atom changing the volume of the unit cell, a higher multiplier was applied for the recommended cutoff (2 times the default value, instead of 1.125 times, for each metal), due to the slower convergence of the stress tensor with respect to the basis set, which was tested in a previous study done by other authors; 133 (ii) to calculate the clean surface properties discussed in Chapter 6 the cutoff was adjusted to be 12.5 % higher than the required cutoff for each metal (for example, 402, 282 and 280 eV were employed, respectively, to calculate the clean Ni(111), Pd(111) and Pt(111) surface properties), since there is no need to comply with a higher cutoff in a self-contained investigation of the clean surface properties; (iii) the results shown in Chapter 3 employed a cutoff energy 12.5 % higher than the recommended cutoff, ENMAX, for each metal, since the O atom was not studied in the referred chapter.…”
Section: Adjusting the Cutoff Energy For The Basis Set And Sampling The Brillouin Zonementioning
confidence: 99%
“…The choice of the 12.5 % multiplier is based on several previous studies of the properties of transition-metal bulks, surfaces and nanoclusters reported extensively in the literature 35,37,[133][134][135][136][137] This allowed the quick selection of well-converged computational parameters for the present study. Here, we selected some model systems to demonstrate the convergence of the properties with respect to the most important computational parameters.…”
Section: Adjusting the Cutoff Energy For The Basis Set And Sampling The Brillouin Zonementioning
confidence: 99%
See 2 more Smart Citations